Association between alcohol consumption during pregnancy and risks of congenital heart defects in offspring: meta-analysis of epidemiological observational studies. Issue 1 (December 2016) - Wen, Zhongyuan; Yu, Di; Zhang, Weiyan; Fan, Changfeng; Hu, Liang; Feng, Yu; Yang, Lei; Wu, Zeyu; Chen, Runsen; Yin, Ke-jie; Mo, Xuming
Abstract Background To explore the association between maternal alcohol consumption and/or binge drinking and congenital heart defects (CHDs), we conducted a meta-analysis for more sufficient evidence on this issue. Methods We searched Medline, EMBASE, and the Cochrane Library from their inceptions to December 2014 for case-control and cohort studies that assessed the association between maternal alcohol consumption and CHD risk. Study-specific relative risk estimates were calculated using random-effect or fixed-effect models. Results A total of 19 case-control studies and 4 cohort studies were included in the meta-analysis. We observed a null association between maternal alcohol consumption during pregnancy and the risk of CHDs. Even in the analysis of different trimesters of pregnancy, we found little association between the two. Conclusions This meta-analysis suggests that maternal alcohol consumption is modestly not associated with the risk of CHDs. However, further investigation is needed to confirm this conclusion.